5 ( × - 1 ) = 3× + 5
Soluções para a tarefa
Respondido por
0
Resolução:
5(x - 1) = 3x + 5
5x - 5 =3x + 5
5x - 3x = 5 + 5
2x=10
![x= \frac{10}{2} x= \frac{10}{2}](https://tex.z-dn.net/?f=x%3D+%5Cfrac%7B10%7D%7B2%7D+)
![x=5 x=5](https://tex.z-dn.net/?f=x%3D5)
prova real:
5( 5 -1) = (3*5) + 5
25 - 5 =15 + 5
20 = 20
5(x - 1) = 3x + 5
5x - 5 =3x + 5
5x - 3x = 5 + 5
2x=10
prova real:
5( 5 -1) = (3*5) + 5
25 - 5 =15 + 5
20 = 20
Respondido por
0
digamos q o (X) é igual a 1
ex :
5(x-1)=3x+5
5(1-1)=3*1+5
=5=3+5
=5=6
5+6
=11
ex :
5(x-1)=3x+5
5(1-1)=3*1+5
=5=3+5
=5=6
5+6
=11
Perguntas interessantes